Noninvasive estimation of brain organ weights by postmortem magnetic resonance imaging compared to conventional autopsy in fetuses and neonates. (December 2018) - Lim, Philip; Chang, Allison; Lim, Ryan; Washington, Kathleen A.; Miller, Sarah E.; Connor, Joseph; Ward, Chelsea
Abstract : Estimating brain organ weight with a 1.5 T MRI is accurate. There is an average 14% over-estimated brain organ weight by MRI. For fetuses ≤20 weeks gestation, there is 17.5% overestimation of brain weight. For fetuses >20 weeks gestation, there is a 10.9% overestimation of brain weight.